Mapping and Analyzing Spatial Variability of Peat Depths by Using Geostatistics - Armanto, M Edi; Setiabudidaya, Dedi; Ngudiantoro; Wildayana, Elisa; Zuhdi, Mohd (Journal of Smart Agriculture and Environmental Technology, 2024)
Determining peat depths can be done by intensive surveys which are expensive, inefficient, and ineffective, therefore, it is essential to find simple alternative methods for measuring peat depths. The research objective was to estimate and make maps of peat depths by applying Geostatistics analysis. This research was conducted on Muaro Jambi District, Jambi (Seponjen Village, Kumpeh) peatlands. The primary data was analyzed by ArcGIS 10.3 and Geostatistics programs. The spatial variability of peat depths on Site A (peat depth of 8.10–15.00 m) and Site B (3.10–8.00 m) showed maximum values at 271 and 242 m distances, respectively. On-Site C (0.00–3.00 m), maximum variability was found at the distance of 63 m. Peat depths variability may be interpolated at a maximum of 271 m (for Site A) and 242 m (for Site B). More than the above distances, peat depths cannot be interpolated. Site A must be conserved because of peat depths of > 3 m, only Site C can be cultivated for agriculture and plantations. Unfortunately, all areas have been cultivated for the oil palm plantation because the government has granted concession permits to plantations before knowing how deep the permissible peatlands are for the whole area.